2023
DOI: 10.1021/acsnano.3c02066
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Bridged Stabilization of Single Atomic W on Rh Metallenes for Robust and Efficient pH-Universal Hydrogen Evolution

Abstract: Highly efficient and durable electrocatalysts are of the utmost importance for the sustainable generation of clean hydrogen by water electrolysis. Here, we present a report of an atomically thin rhodium metallene incorporated with oxygenbridged single atomic tungsten (Rh−O−W) as a high-performance electrocatalyst for pH-universal hydrogen evolution reaction. The Rh−O−W metallene delivers ascendant electrocatalytic HER performance, characterized by exceptionally low overpotentials, ultrahigh mass activities, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Furthermore, X-ray photoelectron spectroscopy (XPS) was further conducted to investigate the chemical state and electronic state of the Rh-GB NSs. As exhibited in Figure S5, the main peaks at 307.1 and 311.9 eV corresponded to 3d 5/2 and 3d 3/2 peaks of metallic Rh, respectively. , The peaks at approximately 307.8 and 313.1 eV were assigned to Rh 3+ , which can be attributed to surface oxidation when exposed to air. The peak areas indicated that metallic Rh was the predominant species in the Rh-GB NSs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, X-ray photoelectron spectroscopy (XPS) was further conducted to investigate the chemical state and electronic state of the Rh-GB NSs. As exhibited in Figure S5, the main peaks at 307.1 and 311.9 eV corresponded to 3d 5/2 and 3d 3/2 peaks of metallic Rh, respectively. , The peaks at approximately 307.8 and 313.1 eV were assigned to Rh 3+ , which can be attributed to surface oxidation when exposed to air. The peak areas indicated that metallic Rh was the predominant species in the Rh-GB NSs.…”
Section: Resultsmentioning
confidence: 99%
“…The total density of states (DOS) of the Ru-WC x catalyst shows a higher occupation at the Fermi level compared with WC x and Ru, suggesting that the electronic coupling between Ru and W atoms reduces the charge transfer resistance (Figure 5c). [26] Noticeably, the d-band center of Ru-WC x (Ru) is lower than metallic Ru in the partial density of states (PDOS) plot (Figure 5d and 5e). Based on the d-band theory, the decline of the d-band center implies that the adsorption of reaction intermediates on the Ru site is weakened, promoting the subsequent evolution steps of H 2 O or H 2 .…”
Section: Methodsmentioning
confidence: 95%
“…Fourier-transformed and wavelet-transformed EXAFS commonly reveals changes in intensity and radial distance of metal–oxygen and metal–metal coordination, presenting an insightful picture of the catalyst's structural evolution under electrochemical conditions. 75,76 With the aid of in situ Raman 77,78 and in situ Fourier transform infrared spectroscopies 79 in probing the formation of oxygenated and carbonated species, the dynamic chemistry of the electrified interface can be fully unravelled.…”
Section: Study Of Surface Dynamicsmentioning
confidence: 99%